Dynamical systems : theory, applications and future directions - Tchuenche, Jean Michel (Mathematics research developments series., 2013)
Virtually any advance in disease dynamics requires a sophisticated mathematical approach in order to map out the parameters that drive the system. This book exploits some of the fundamental theory of dynamical systems and applies them to biological and social sciences. Topics include the asymptotic stability of almost periodic systems; modeling and vibration-based system identification and damage inspection of flexible structures; the stability and persistence of dynamical systems using Lyapunov functions; Krylov and Schur subspaces in construction of prediction error filter and its computatio.